Efficacy of closed cell wet-suit at various depths and gas mixtures for thermoprotection during military training dives - Kelly, Karen R.; Palombo, Laura J.; Jensen, Andrew E.; Bernards, Jake R. (Frontiers in Physiology, 2023)
Purpose: To evaluate a closed-cell wet-suit for thermal protective capability during extreme cold water exposure at various depths. Methods: Thirteen (n = 13) elite military divers who were tasked with cold-water training, participated in this study. To mimic various depths, the Ocean Simulation Facility (OSF) at the Navy Experimental Diving Unit (NEDU) was pressurized to simulate dive depths of 30, 50, and 75fsw. Water temperature remained at 1.8–2.0°C for all dives. Four divers dove each day and used the MK16 underwater breathing apparatus with gas mixes of either N202 (79:21) or HeO2 (88:12). Mean skin temperature (TSK) (Ramanathan, 1964), core temperature (Tc), hand and foot readings were obtained every 30 min for 30 and 50fsw and every 15 min during the 75fsw dive. Results: TC was significantly reduced across all dives (p = 0.004); however, was preserved above the threshold for hypothermia (post dive Tc = 36.5 ± 0.4). There was no effect of gas mix on TC. TSK significantly decreased (p < 0.001) across all dives independent of depth and gas. Hand and foot temperatures resulted in the termination of three of the dives. There were no significant main effects for depth or gas, but there were significant main effects for time on hand temperature (p < 0.001) and foot temperature (p < 0.001). Conclusion: Core temperature is maintained above threshold for hypothermia. Variatioins in TC and TSK are a function of dive duration independent of depth or gas for a closed-cell wet-suit in cold water at various depths. However, both hand and foot temperatures reached values at which dexterity is compromised.